The Corrosive Properties Analysis of Biodegradable Magnesium Composites Mg-xCAp (x=0, 5%, 10%, and 15%) for Bone Implant Applications - Ana Bano; Ni Nyoman Rupiasih; Iwan Setyadi; Mirza Wibisono; Suryadi Suryadi; I Nyoman Jujur (BULETIN FISIKA, 2026)
Magnesium (Mg) is a promising biodegradable material for bone implant applications due to its suitability of mechanical properties and biocompatibility with natural bone. However, its rapid degradation in physiological environments remains a major obstacle in clinical applications. The addition of carbonated apatite (CAp) as a bioactive reinforcing phase is expected to improve the corrosion resistance of Mg-based composites by forming a more stable surface layer. This study aims to evaluate the corrosion properties of Mg–xCAp composites with variations in CAp content of 0%, 5%, 10%, and 15%. Corrosion testing was carried out electrochemically in simulated body fluid (SBF) solutions using the Open Circuit Potential (OCP), Electrochemical Impedance Spectroscopy (EIS), and Tafel polarization methods. The OCP results showed a potential shift towards a more positive direction up to −1.87 V as the CAp fraction increased, indicating increased electrochemical stability. EIS analysis showed a progressive increase in charge transfer resistance (Rct), with the highest value of 309.8 Ω•cm² in the Mg–15CAp composite, indicating the formation of a more protective surface layer against aggressive ion penetration. Tafel polarization results confirmed a significant decrease in corrosion rate, with Mg–15CAp showing the lowest corrosion rate of 2.03 mm/year. Overall, the addition of CAp proved effective in controlling Mg degradation and improving the corrosion resistance of the composite, thus potentially expanding the application of Mg–CAp as a biodegradable bone implant material.